Multipoint Observations of the June 2012 Interacting Interplanetary Flux Ropes - Kilpua, Emilia K. J.; Good, Simon W.; Palmerio, Erika; Asvestari, Eleanna; Lumme, Erkka; Ala-Lahti, Matti; Kalliokoski, Milla M. H.; Morosan, Diana E.; Pomoell, Jens; Price, Daniel J.; Magdalenić, Jasmina; Poedts, Stefaan; et al. (Frontiers in Astronomy and Space Sciences, 2019)
We report a detailed analysis of interplanetary flux ropes observed at Venus and subsequently at Earth's Lagrange L1 point between June 15 and 17, 2012. The observation points were separated by about 0.28 AU in radial distance and 5° in heliographic longitude at this time. The flux ropes were associated with three coronal mass ejections (CMEs) that erupted from the Sun on June 12–14, 2012 (SOL2012-06-12, SOL2012-06-13, and SOL2012-06-14). We examine the CME–CME interactions using in-situ observations from the almost radially aligned spacecraft at Venus and Earth, as well as using heliospheric modeling and imagery. The June 14 CME reached the June 13 CME near the orbit of Venus and significant interaction occurred before they both reached Earth. The shock driven by the June 14 CME propagated through the June 13 CME and the two CMEs coalesced, creating the signatures of one large, coherent flux rope at L1. We discuss the origin of the strong interplanetary magnetic fields related to this sequence of events, the complexity of interpreting solar wind observations in the case of multiple interacting CMEs, and the coherence of the flux ropes at different observation points.